The Impact of Constitutional Court Decision No. 90/PUU-XXI/2023 on Judicial Dignity and Constitutional Legitimacy - Muhammad Amiril A'la (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The decision made by the Constitutional Court in examining the minimum age limit for presidential candidates and vice presidents in Article 169 letter q of the Election Law, as outlined in Decision Number 90/PUU-XXI/2023, is legally flawed. This is due to a violation of the code of ethics by one of the Constitutional Court Judges during the case's examination and decision-making process. Moreover, the age limit for presidential candidates and vice presidents, which is regulated in Article 169 Letter Q of the Election Law, is part of an open legal policy. Therefore, the Constitutional Court does not have the right to change or decide the case. This has significant implications for the temper of the Constitutional Court. To address the problematic decision and the violations of the code of ethics, the Constitutional Court Ethics Council is taking steps to improve the tarnished image of the Constitutional Court caused by Decision Number 90/PUU-XXI/2023